2022
DOI: 10.3390/brainsci12010106
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Outcomes of Patients with Chronic Obstructive Pulmonary Disease

Abstract: Introduction: Research has shown that patients with ischemic stroke and coexisting obstructive respiratory disorders have worse clinical status on admission and increased long-term mortality. Patients with chronic obstructive pulmonary disease (COPD) are at increased risk of stroke, and the risk is even greater after exacerbation of COPD. Moreover, COPD and stroke share major risk factors, which are advancing age and smoking. The aim of this study was to analyze the incidence of complications and mortality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Firstly, the airway structure of COPD patients is significantly different from the normal population, and the incidence of post-stroke pneumonia is significantly higher due to airway spasms, destruction and collapse of the airway wall, poor cilia function, and sputum aggregation. [9,45] Secondly, some studies have also reported that COPD patients' mortality may be associated with post-stroke complications such as urinary tract infection, acute heart attack, and congestive heart failure. [26,36] Therefore, these comorbidities in COPD patients may increase the risk of post-stroke death.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the airway structure of COPD patients is significantly different from the normal population, and the incidence of post-stroke pneumonia is significantly higher due to airway spasms, destruction and collapse of the airway wall, poor cilia function, and sputum aggregation. [9,45] Secondly, some studies have also reported that COPD patients' mortality may be associated with post-stroke complications such as urinary tract infection, acute heart attack, and congestive heart failure. [26,36] Therefore, these comorbidities in COPD patients may increase the risk of post-stroke death.…”
Section: Variablesmentioning
confidence: 99%
“…Some studies have shown that patients with COPD have an increased risk of death after stroke. [8,9] However, other studies possess a different view. [10] Therefore, we systematically evaluated the literature on the risk of stroke in COPD patients, the correlation between AECOPD and stroke risk, short-term mortality risk after stroke in COPD patients, and long-term mortality risk after stroke in COPD patients; to comprehensively explore the relationship between COPD and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the predictors of infection in stroke patients revealed that nasogastric tube use, atrial fibrillation, total anterior circulation syndrome, and urinary catheter usage increased the risk of post-stroke infection [ 10 ]. Another meta-analysis on risk factors for post-stroke pneumonia showed that advanced age, male sex, stroke severity, dysphagia, nasogastric tube use, diabetes, mechanical ventilation, smoking, chronic obstructive pulmonary disease, and atrial fibrillation are predictors [ 11 , 12 , 13 ]. However, most studies focused on pneumonia, and research on all-cause post-stroke infections is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients with COPD were reportedly at a higher risk of developing stroke, [1] and patients with stroke and underlying COPD were at a higher risk of in-hospital complications and mortality than those without COPD. [2][3][4] The mainstream therapy for stable-state COPD is a combination of inhalers depending on the severity of the disease. [5] Inhalers have been demonstrated to improve COPD outcomes, including improving respiratory symptoms and quality of life, reducing the frequency of acute exacerbations, and reducing mortality.…”
Section: Introductionmentioning
confidence: 99%